Performa Pertumbuhan Kukang Jawa (Nycticebus javanicus E. Geoffroy,1812) yang Diberi Tambahan Biskuit dan Monkey Chow dalam Pakan - Farida, Wartika Rosa; Astuti, Wulansih Dwi; Sari, Andri Permata (JURNAL BIOLOGI INDONESIA, 2014)
This study aims to determine the effect of the addition of biscuits and monkey chow in the feed to the growthperformance of java slow loris (Nycticebus javanicus E. Geoffroy, 1812). Research has been conducted in CaptivitySmall Mammals, Zoology Division, Research Center for Biology - LIPI for 52 days consisted of a 10 days period offeed adaptation and 42 days (6 weeks) period of data collection. The material used is six java slow loris aged 1 - 1,5years consisted of three males and three females. Alternative feed given during the study were banana (Musa sp.),papaya (Carica papaya), fuji apple (Malus domestica), pear (Pyrus amygdaliformis), guava (Psidium guajava),cucumber (Cucumis sativus), sweet potato (Ipomea batatas), boiled quail eggs, biscuits sprinkled with sugar, monkeychow, crickets, and mealworm. Parameters measured were feed intake, body weight gain, feed efficiency, and totaldigestible nutrients (TDN). The data were analyzed using analysis of variance, followed by Duncans multiplerange test. The results showed the average of dry matter intake in PII (45.89 g / head / day) was significantly higher(P <0.05) than that in PI (43.19 g / head / day) and P0 (42,17g / head / day. The average of body weight gain ofslow loris in PI> PII> P0, namely respectively 3.49 g / head / day, 3.41 g / head / day, and 3.15 g / head / day,while the feed efficiency in the treatment PI> P0> PII, respectively 8.20%, 7.47%, and 7.44%. The average oftotal digestible nutrients (TDN) of slow loris in PI (96.33%) was significantly higher (P <0.05) than that in PII(92.91%) and P0 (85.50%). The data of nutrient consumption can be used as a basis for the preparation of rationsand feed for slow loris in captivity.Key words: growth, feed efficiency, Nycticebus javanicus, captive breeding